Pengaruh Tingkat Literasi Wisata Halal, dan Perilaku Wisatawan Terhadap Minat Berwisata Halal di Provinsi Riau - Riansyah, Abdi; Ismail, Nurizal (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
This research aims to analyze the effect level of halal tourism literacy and tourist behavior towards interest in visiting halal tourism with a focus on halal tourism in Riau Province. This research uses the PLS-SEM (Partial Least Square Structural Equation Modeling) method to illustrate the results of regression analysis related to testing the relationship between independent and dependent variables. The results of this research reveal that the variables of halal tourism literacy and tourist behavior have a significant effect on interest in visiting halal tourism, which means that the better the public's literacy towards halal tourism, the better the public's attitude towards halal tourism. Vice versa, the better the public's attitude towards halal tourism, the higher the interest in visiting halal tourism. Therefore, it is important to cultivate a positive image of halal tourism to ensure halal tourism in Indonesia, especially in Riau Province.